Role of the renin-angiotensin system in the development of severe COVID-19 in hypertensive patients - Silva-Aguiar, Rodrigo Pacheco (Am J Physiol Lung Cell Mol Physiol, 2020)
A new form of severe acute respiratory syndrome (SARS) caused by SARS-coronavirus 2 (CoV-2), called COVID-19, has become a global threat in 2020. The mortality rate from COVID-19 is high in hypertensive patients, making this association especially dangerous. There appears to be a consensus, despite the lack of experimental data, that angiotensin II (ANG II) is linked to the pathogenesis of COVID-19. This process may occur due to acquired deficiency of angiotensin-converting enzyme 2 (ACE2), resulting in reduced degradation of ANG II. Furthermore, ANG II has a critical role in the genesis and worsening of hypertension. In this context, the idea that there is a surge in the level of ANG II with COVID-19 infection, causing multiple organ injuries in hypertensive patients becomes attractive. However, the role of other components of the renin angiotensin system (RAS) in this scenario requires elucidation. The identification of other RAS components in COVID-19 hypertension may provide both diagnostic and therapeutic benefits. Here, we summarize the pathophysiologic contributions of different components of RAS in hypertension and their possible correlation with poor outcome observed in hypertensive patients with COVID-19.